Potential of Methane (CH4), Nitrogen (N2), and Carbon Dioxide (CO2) from Eco-Enzyme with the Addition of Cow Feces Starter - Kamelia, Marlina; Ulmillah, Aulia; Suci Wulan Pawhestri (Pusat HKI, Paten, dan Publikasi Ilmiah Universitas Islam Negeri Raden Intan Lampung, 2025)
Eco-enzyme solutions are commonly utilized as disinfectants, cleaners, and liquid fertilizers; however, their potential as substrates for biogas production remains underexplored. This study evaluated the methane (CH₄), carbon dioxide (CO₂), nitrogen (N₂), pH, temperature, and gas pressure generated from eco-enzyme–based anaerobic fermentation supplemented with cow manure as a microbial starter. A quantitative experimental design with five treatments and direct observational measurements was employed, and data were analyzed descriptively. Results showed that methane production was generally low, with the highest concentration observed in treatment P5 (2.889%). The highest gas pressure was also recorded in P5 (70 mL). Nitrogen dominated the gas composition (95.875–99.669%), while CO₂ ranged from 0.237 to 4.125%. These findings indicate that eco-enzyme combined with cow manure produces low CH₄ levels, suggesting that further optimization of substrate composition and fermentation conditions is needed to enhance biogas quality.